(untitled) (Medico Legal Update, 2021)
Background: Lead and it’s compound induced health problems are continue to be an important, preventable public health issue. The common source of lead exposure in modern days is cosmetic products. Aim and Objectives: The study aims to evaluate the awareness about the adverse effects of lead-containing cosmetics in adolescence and the young adult population including factors influencing customers, knowledge about the product ingredients, and quality. Materials and Method: In this study, a questionnaire was prepared using Google form and circulated among the adolescence and young adult subjects to assess the awareness about the adverse effect of lead in cosmetics. The study sample comprised of totally 203 participants of both males and females with the age group between 16 to 24 years. Results: In this study, it is found that 87% of the participants were aware that cosmetic products harm their health. 78% of the participants know lead and its compounds present in the cosmetics. 86% of participants have the habit of checking the ingredients and quality of cosmetic products. About 96% of the participants were influenced by the advertisement of the product before buying it.